Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

If $\triangle$ be the area of $\triangle ABC$ with side lengths $a,b,c$. Then show that $\displaystyle \triangle\leq \frac{1}{4}\sqrt{(a+b+c)\cdot abc}$

and also show that equality hold if $a=b=c$.

$\bf{My\; Try}::$ Here we have to prove $4\triangle\leq \sqrt{(a+b+c)\cdot abc}$

Using the formula $$\triangle = \sqrt{s(s-a)(s-b)(s-c)}$$, where $$2s=(a+b+c)$$

So $$4\triangle = \sqrt{2s(2s-2a)(2s-2b)(2s-2c)}=\sqrt{(a+b+c)\cdot(b+c-a)\cdot(c+a-b)\cdot(a+b-c)}$$

Now using $\bf{A.M\geq G.M}$ for $(b+c-a)\;,(c+a-b)\;,(a+b-c)>0$

$$\displaystyle \frac{(b+c-a)+(c+a-b)+(a+b-c)}{3}\geq \sqrt[3]{(b+c-a)\cdot(c+a-b)\cdot(a+b-c)}$$

So we get $\displaystyle (a+b+c)\geq 3\sqrt[3]{(b+c-a)\cdot(c+a-b)\cdot(a+b-c)}$

But i did not understand how can i prove above inequality

help Required


share|cite|improve this question
Just a thought, a triangle with sides $s-a$, $s-b$, $s-c$, has the area $\sqrt{(a+b+c)\cdot abc}$. – Sawarnik Feb 25 '14 at 9:17
up vote 6 down vote accepted

For a triangle

$\Delta = \frac{abc}{4R} = rs$

Now in your inequality you can put in the values to get

$R \ge 2r$

This is known to be true since the distance between incentre and circumcentre $d^2 = R(R-2r)$

Thus your inequality is proved

share|cite|improve this answer
Thanks user2369284. have you any link or pdf how can we prove $d^2=R(R-r)$, Thanks – juantheron Dec 29 '13 at 10:48
@juantheron Link is's_theorem_in_geometry – user2369284 Dec 29 '13 at 10:51
Thanks user2369284 – juantheron Dec 29 '13 at 11:57

It helps to write down what you want to prove:

$$(b+c-a)(c+a-b)(a+b-c) \le abc$$

You viewed the left-hand expression as a geometric mean, but replacing it by a arithmetic mean does not work because the resulting inequality is an AM-GM inequality in the wrong direction, so you need to try something else.

There are many ways to proceed, but a good routine first step is a substitution that replaces $a, b, c$ who are linked by triangle inequalities with $2x=b+c-a$, $2y=c+a-b$, $2z=a+b-c$ who are simply positive numbers.

The desired inequality becomes:

$$8xyz \le (y+z)(x+z)(x+y).$$

But this is simply a product of three AM-GM inequalities:

$$\sqrt{yz}\sqrt{xz}\sqrt{xy}\le \frac{y+z}2\frac{x+z}2\frac{x+y}2.$$

So everything is proved.

Alternatively, if you do not see it, you can simply expand the product and apply one AM-GM inequality to the 8 terms.

share|cite|improve this answer

Thanks mathlove,phira,and user for solution.

My prove for $(b+c-a)\cdot(c+a-b)\cdot(a+b-c)\leq abc$, where $a,b,c$ are the sides of a $\triangle$.

Using $\;\;\;\; \{b+(c-a)\}\cdot \{b-(c-a)\} = b^2-(c-a)^2\leq b^2$

similarly $ \{c+(a-b)\}\cdot \{c-(a-b)\} = c^2-(a-b)^2\leq c^2$

similarly $\{a+(b-c)\}\cdot \{a-(b-c)\} = a^2-(b-c)^2\leq a^2$

Multimply these three equations, we get $(b+c-a)\cdot(c+a-b)\cdot(a+b-c)\leq abc$

and equality hold when $a=b=c$

share|cite|improve this answer
That is a nice proof. – Phira Dec 29 '13 at 10:56

We know $$S=\frac{\sqrt{(a+b+c)(-a+b+c)(a-b+c)(a+b-c)}}{4}.$$

So, all we need is to prove the following : $$(-a+b+c)(a-b+c)(a+b-c)\le abc.$$

This is a well known inequality. Proof is here.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.